A self-repairing super-hydrophobic nano anti-corrosion coating and preparation method thereof
A multi-layer structured self-repairing super-hydrophobic nano anti-corrosion coating with nanoparticles and micron particles addresses hydrophobicity loss and secondary damage, ensuring effective and durable repair responses.
Patent Information
- Application Number
- CN202411020456.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-07-29
AI Technical Summary
Existing self-repairing super-hydrophobic nano anti-corrosion coatings suffer from decreased hydrophobicity and are prone to secondary damage after microcapsule repair, with suboptimal mechanical properties and encapsulation efficiency.
A self-repairing super-hydrophobic nano anti-corrosion coating composed of organic fluorine-silicon modified acrylic resin, hydrophobic nano-SiO2, microcapsules with multi-layer core and wall structures containing nanoparticles and micron particles, and a platinum-based catalyst, which enhances hydrophobicity and mechanical properties through controlled release of repair agents.
The coating maintains hydrophobicity, prevents secondary damage, and extends service life by providing rapid and precise repair responses to various damage levels, improving self-repair efficiency and durability.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to a self-repairing super-hydrophobic nano anti-corrosion coating and a preparation method thereof. Background Art
[0002] Self-repairing anti-corrosion coating is a smart material with self-repairing ability. Its basic principle is that when the coating is damaged or destroyed, it can automatically trigger the repair mechanism to restore the integrity and anti-corrosion function of the coating. This self-repairing ability enables the coating to have a longer service life and better protection effect under complex and changing environmental conditions.
[0003] Microcapsule-filled self-healing coating is a common self-healing coating currently. It encapsulates the repair agent in microcapsules, and compounds the microcapsules and the catalyst that can polymerize the repair agent in the polymer material. When the polymer is subjected to external forces and cracks are generated inside it, the microcapsules rupture under the action of the cracks, and the repair agent is released under the action of siphoning and fills the inside of the cracks, and then reacts with the catalyst in the matrix material to initiate polymerization, thereby repairing the cracks and restoring the performance of the coating. However, the core component of the microcapsule is single, mostly a single resin, the self-healing effect is not ideal, the mechanical properties are poor, and the bonding force with the matrix resin is poor. Moreover, the emulsion is difficult to stabilize in the traditional microcapsule preparation method, resulting in low encapsulation efficiency.
[0004] The invention patent of China Patent Announcement No. CN110484042B discloses a self-repairing super-hydrophobic nano anti-corrosion coating and its preparation method. First, a microcapsule is prepared, and then the microcapsule is mixed with an organic fluorine-silicon modified acrylic resin, a hydrophobic nano-SiO 2 , xylene and platinum-based catalyst are mixed to prepare a self-repairing super-hydrophobic nano anti-corrosion coating. The invention uses a mixture of dimethyl silicone oil and corrosion inhibitor as the capsule core, which not only realizes the uniform dispersion of the corrosion inhibitor in the matrix resin, but also realizes the self-repair of the coating surface, which can effectively avoid losses during service and transportation; the process described in the invention is simple, energy-saving and environmentally friendly, and suitable for large-scale production. After the self-repairing super-hydrophobic nano anti-corrosion coating of the invention is made into a coating, the coating has good mechanical properties and good anti-corrosion effect. The impedance repair efficiency of the coating can reach 98%, and the fracture toughness repair efficiency can reach 99%.
[0005] Although the above scheme improves the repair performance of the microcapsules to a certain extent, the hydrophobicity of the self-repairing super-hydrophobic nano anti-corrosion coating decreases after self-repair, making it prone to secondary damage. Summary of the invention
[0006] The embodiments of the present application provide a self-repairing super-hydrophobic nano-anti-corrosion coating and a preparation method thereof, thereby solving the problem in the prior art that the hydrophobicity of the coating decreases and it is prone to secondary damage after microcapsule repair. This achieves the effect of enhancing the hydrophobicity of the coating, preventing secondary damage, extending the service life of the coating, and improving the repair efficiency and repair performance.
[0007] The present invention provides a self-repairing super-hydrophobic nano anti-corrosion coating, which is composed of organic fluorine-silicon modified acrylic resin, hydrophobic nano-SiO 2 , microcapsules containing particles of different sizes, xylene and platinum-based catalysts.
[0008] Furthermore, the core of the microcapsule is dimethyl silicone oil, a corrosion inhibitor mixture and nanoparticles, and the capsule wall is polyurea formaldehyde and micron particles; the corrosion inhibitor is benzotriazole; wherein both the nanoparticles and micron particles include silicon dioxide and titanium dioxide; wherein the particle size of the nanoparticles is nanometer-level, and the particle size of the micron particles is micrometer-level.
[0009] The preparation method of the above self-repairing super-hydrophobic nano anti-corrosion coating specifically comprises:
[0010] S1. Preparation of microcapsules;
[0011] S11. A urea-formaldehyde prepolymer solution is prepared from urea, formaldehyde and micron particles;
[0012] Specifically, urea, formaldehyde and micron particle solution are mixed in a mass ratio of (0.5-1.5): (1.5-2.5): (0.05-0.3), the pH of the mixed solution is adjusted to 8.0-9.0, and the mixture is placed at 60°C-80°C for reaction for 0.5h-1.5h, and after cooling, a surfactant with a mass fraction of 0.6%-1.3% is added, and the urea formaldehyde prepolymer solution is obtained after dilution; the particle size of the micron particles is 0.1-10μm;
[0013] S12. The dimethyl silicone oil, the corrosion inhibitor and the nanoparticles are mixed and dried to obtain a capsule core, and the capsule core is added to the urea formaldehyde prepolymer solution and mixed, emulsified, polycondensed, washed, filtered, and dried to obtain a microcapsule;
[0014] The mass ratio of urea formaldehyde prepolymer, dimethyl silicone oil, corrosion inhibitor and nanoparticles is (80-100): (8-10): (4-5): (1-5); the particle size of the nanoparticles is 5-100 nm; the emulsification temperature is 25°C-35°C; the emulsification time is 5-20 min; the pH of the polycondensation emulsion is 2.0-2.5, the polycondensation temperature is 70°C-75°C, and the polycondensation time is 3-4 h;
[0015] S2. Preparation of self-repairing super-hydrophobic nano-anticorrosive coating;
[0016] Specifically, organic fluorine-silicon modified acrylic resin, xylene, hydrophobic nano-SiO 2 The microcapsules and platinum-based catalyst are mixed in a mass ratio of (80-100):(20-30):(1-2):(5-7):(2-4), stirred at 1000-1500 rpm for 1-2 hours, and then ultrasonicated at 60-100 kHz for 30-40 minutes to obtain the product.
[0017] Furthermore, the capsule core obtained in step S12 is used as the inner capsule core, and is repeatedly added into dimethyl silicone oil, corrosion inhibitor and nanoparticles to mix and dry to obtain a multilayer capsule core, wherein the number of repetitions is one or more, and the particle size of the nanoparticles during repeated addition increases with the number of additions, and the particle size of the nanoparticles of the inner layer capsule core is 5-10nm; the multilayer capsule core is added into a urea formaldehyde prepolymer solution for emulsification, polycondensation, washing, filtering and drying to obtain a multilayer capsule core microcapsule.
[0018] Furthermore, the particle size of the nanoparticles during repeated addition increases with the number of additions. Specifically, the particle size of the nanoparticles after repeated addition is n times the particle size of the nanoparticles in the inner capsule core, where n is the number of repeated additions; and n is less than 6.
[0019] Furthermore, the microcapsules obtained in step S12 are added again to the urea formaldehyde prepolymer solution for mixing, emulsification, polycondensation, washing, filtering and drying to obtain multi-layer capsule wall microcapsules; the number of times of adding again is one or more times.
[0020] Furthermore, the micron particle size of the urea formaldehyde prepolymer solution is different when it is added again.
[0021] Furthermore, the multilayer capsule core microcapsules obtained in step S12 are added to dimethyl silicone oil, corrosion inhibitor and nanoparticles, mixed and dried to obtain multilayer capsule core microcapsules wrapped with capsule cores; the microcapsules are further placed in a urea formaldehyde prepolymer solution for emulsification, polycondensation, washing, filtering and drying to obtain multilayer composite microcapsules.
[0022] Furthermore, the mass ratio of the urea-formaldehyde prepolymer, dimethyl silicone oil, corrosion inhibitor and nanoparticles is (20-50):(8-10):(4-5):(1-5); the particle size of the micron particles in the urea-formaldehyde prepolymer is 5-10 μm.
[0023] Furthermore, the emulsification temperature is 25°C-35°C; the emulsification time is 5-20min; the pH of the polycondensation emulsion is 2.0-2.5, the polycondensation temperature is 60°C-70°C, and the polycondensation time is 2-3h.
[0024] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0025] First, nanoparticles have an extremely small particle size and can fill the tiny gap between the microcapsule wall and the capsule core, thereby enhancing the sealing of the microcapsule. When the microcapsule ruptures and releases the repair agent, the nanoparticles can flow out with the repair agent, filling the cracks and enhancing the repair effect. By adjusting the particle size and content of nano- and micron-particles, the structure and properties of the microcapsule can be regulated. The combination of nanoparticles and micron-particles makes the rupture of the microcapsule and the release of the repair agent more uniform and rapid.
[0026] Secondly, the multi-layer core structure enables the microcapsules to respond to coating damage at different levels. The larger-sized nanoparticles contained in the outer core are more likely to respond to large-scale cracks or damage in the coating, and quickly release the repair agent for initial repair. The smaller-sized nanoparticles contained in the inner core can provide supplementary repair, fill small-scale damage, or provide lasting repair effects in more serious damage. The multi-layer core forms a graded response mechanism to improve the overall protective capability of the coating.
[0027] Third, the different micron particle sizes in the multi-layer capsule wall structure can affect the release performance of the repair agent, allowing the repair agent to be released in a more controllable manner. Micron particles of different sizes in the multi-layer capsule wall have different response speeds to cracks. When the coating is damaged, the outer capsule wall responds to the cracks and promotes the rupture of the microcapsules, while the inner capsule wall can control the release rate of the repair agent, thereby achieving more precise and effective repair.
[0028] Fourthly, the two layers of capsule walls in the multi-layer composite microcapsule contain capsule cores, i.e., repair agents, and the outermost capsule wall is easy to rupture; when the coating is damaged and needs to be repaired quickly, the multi-layer composite microcapsules can be directly applied to the damaged area, and the repair agent in the capsule core layer released after the outermost capsule wall ruptures can directly repair the damage, significantly shortening the response time and improving the self-repair efficiency; after the outermost capsule wall of the multi-layer composite microcapsule ruptures and releases the capsule core for initial repair, the inner layer still contains complete multi-layer capsule core microcapsules, which can be used as subsequent repair materials to achieve supplementary repair, secondary repair or multiple repairs of the coating, further extending the service life of the coating. DETAILED DESCRIPTION
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0030] Embodiment 1: The present invention relates to a self-healing super-hydrophobic nano-anticorrosive coating, which is composed of an organic fluorine-silicon modified acrylic resin, a hydrophobic nano-SiO 2, microcapsules containing particles of different sizes, xylene and platinum-based catalysts;
[0031] The capsule core of the microcapsule is dimethyl silicone oil, a corrosion inhibitor mixture and nanoparticles, and the capsule wall is polyurea formaldehyde and micron particles; the corrosion inhibitor is benzotriazole; both the nanoparticles and the micron particles include silicon dioxide and titanium dioxide; the particle size of the nanoparticles is nanometer-level, and the particle size of the micron particles is micrometer-level;
[0032] S1. Preparation of microcapsules;
[0033] S11. A urea-formaldehyde prepolymer solution is prepared from urea, formaldehyde and micron particles;
[0034] Specifically, urea, formaldehyde and micron particle solution are mixed in a mass ratio of (0.5-1.5): (1.5-2.5): (0.05-0.3), the pH of the mixed solution is adjusted to 8.0-9.0, and the mixture is placed at 60°C-80°C for reaction for 0.5h-1.5h, and after cooling, a surfactant with a mass fraction of 0.6%-1.3% is added, and the urea formaldehyde prepolymer solution is obtained after dilution; the particle size of the micron particles is 0.1-10μm;
[0035] S12. The dimethyl silicone oil, the corrosion inhibitor and the nanoparticles are mixed and dried to obtain a capsule core, and the capsule core is added to the urea formaldehyde prepolymer solution and mixed, emulsified, polycondensed, washed, filtered, and dried to obtain a microcapsule;
[0036] The mass ratio of urea formaldehyde prepolymer, dimethyl silicone oil, corrosion inhibitor and nanoparticles is (80-100): (8-10): (4-5): (1-5); the particle size of the nanoparticles is 5-100 nm; the emulsification temperature is 25°C-35°C; the emulsification time is 5-20 min; the pH of the polycondensation emulsion is 2.0-2.5, the polycondensation temperature is 70°C-75°C, and the polycondensation time is 3-4 h;
[0037] S2. Preparation of self-repairing super-hydrophobic nano-anticorrosive coating;
[0038] Specifically, organic fluorine-silicon modified acrylic resin, xylene, hydrophobic nano-SiO 2 The microcapsules and platinum-based catalyst are mixed in a mass ratio of (80-100):(20-30):(1-2):(5-7):(2-4), stirred at 1000-1500 rpm for 1-2 hours, and then ultrasonicated at 60-100 kHz for 30-40 minutes to obtain the product.
[0039] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0040] Nanoparticles are added to the capsule core. The specific surface area of nanoparticles is large, which can enhance the dispersion and loading of corrosion inhibitors and dimethyl silicone oil. When the coating is damaged, the nanoparticles can promote the rupture of microcapsules at the cracks and the release of repair agents, quickly repair the damaged coating, quickly release corrosion inhibitors, cover and protect the metal matrix, thereby improving the anti-corrosion performance, self-repair efficiency and response speed of the coating; nanoparticles have extremely small particle sizes and can fill the tiny gaps between the microcapsule wall and the capsule core, enhancing the sealing of the microcapsules; when the microcapsules rupture and release the repair agent, the nanoparticles can flow out with the repair agent, fill the cracks and enhance the repair effect; by adding different nanoparticles, the coating can have different properties, such as adding hydrophobic nano-SiO 2 , which can further improve the hydrophobicity of the coating; at the same time, the addition of nanoparticles can improve the mechanical properties of the coating, making the coating more durable;
[0041] The addition of micron particles to the capsule wall can increase the density of the capsule wall. When the microcapsules are subjected to external forces, the micron particles can effectively disperse the stress, thereby improving the mechanical strength and compressive resistance of the microcapsules and reducing the rupture caused by external forces during transportation and use. The addition of micron particles enables the microcapsules to form a more uniform capsule wall structure, reducing the presence of defects and pores, thereby improving the sealing and stability of the microcapsules and preventing the repair agent from being released prematurely during storage and use. The addition of micron particles can improve the dispersibility of microcapsules in the coating and prevent the microcapsules from agglomerating or precipitating. The capsule wall containing micron particles has surface roughness and wettability, which can enhance the bonding force between the capsule wall and the matrix resin, so that the coating is not easy to fall off or peel off during long-term use, extending the service life of the coating and improving durability.
[0042] By adjusting the particle size and content of nano- and micro-particles, the structure and performance of the microcapsules can be regulated. The combination of nano-particles and micro-particles makes the rupture of the microcapsules and the release of the repair agent more uniform and rapid. After the coating is repaired, the nano-particles and micro-particles cover the surface as a coating. The micro-particles are more likely to adhere to the surface of the carrier. The nano-particles partially adhere to the micro-particle structure. The concave-convex structure of the micro-particles protects the nano-particles and can improve the adhesion of the nano-particles, thereby further improving the repair ability and service life of the coating. At the same time, the combined use of nano-particles and micro-particles forms a dual structure of nano-particles and micro-particles with a certain roughness on the coating surface, which can further enhance the hydrophobicity of the coating. Therefore, the combination of nano-particles and micro-particles improves the self-repairing ability and repair speed of the coating. Under the same repair effect, the amount of microcapsules used in the present application is less, and the nano-particles and micro-particles are insulating materials at room temperature, which reduce the electrochemical corrosion caused by the electric charge, enhance the anti-corrosion performance of the coating, and effectively isolate the erosion of the corrosive medium in a humid environment.
[0043] Embodiment 2: The above embodiment 1 improves the anti-corrosion performance and self-repairing efficiency of the coating by adding nanoparticles and micron particles into the microcapsules, and further optimization is made to improve the self-repairing ability of the coating.
[0044] The capsule core obtained in step S12 is used as the inner capsule core, and is repeatedly added to dimethyl silicone oil, corrosion inhibitor and nanoparticles to mix evenly, and dried to obtain a multilayer capsule core; wherein the number of repetitions is one or more, and the particle size of the nanoparticles during repeated addition increases with the number of additions, and the particle size of the nanoparticles of the inner capsule core is 5-10nm; the multilayer capsule core is added to a urea formaldehyde prepolymer solution for emulsification, polycondensation, washing, filtering, and drying to obtain a multilayer capsule core microcapsule;
[0045] Specifically, the particle size of the nanoparticles after repeated addition increases with the number of additions. Specifically, the particle size of the nanoparticles after repeated addition is n times the particle size of the nanoparticles in the inner capsule core, where n is the number of repeated additions; and n is less than 6.
[0046] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0047] The multi-layer capsule core structure enables the microcapsules to respond to coating damage at different levels. The larger-sized nanoparticles contained in the outer capsule core are more likely to respond to large-scale cracks or damage in the coating, and quickly release the repair agent for initial repair. The smaller-sized nanoparticles contained in the inner capsule core can provide supplementary repair, fill small-scale damage, or provide a lasting repair effect in the case of more serious damage. The multi-layer capsule core forms a graded response mechanism to improve the overall protective ability of the coating.
[0048] The multi-layer capsule core design increases the hierarchical nature of the internal structure of the microcapsule, allowing more repair agents to be effectively carried and dispersed. The distribution of nanoparticles of different sizes at different levels can form a more stable repair agent storage system, so that the repair agent can be evenly and effectively released when needed.
[0049] The multi-layer core structure enables the microcapsules to rupture at different depths and release the repair agent, thereby repairing the coating faster and more effectively. The combination of the rapid response of the outer core and the durable repair of the inner core significantly improves the self-repair ability and response speed of the coating. By adjusting the number of layers and the particle size and distribution of nanoparticles in the core, the release rate and pattern of the repair agent can be controlled, thereby improving the adaptability and flexibility of the coating.
[0050] Embodiment 3: The above embodiment 2 improves the anti-corrosion performance and self-repairing efficiency of the coating by adding nanoparticles of different particle sizes into the capsule core to form a multi-layer capsule core, and further optimizes it to improve the self-repairing ability of the coating.
[0051] The microcapsules obtained in step S12 are added again to the urea formaldehyde prepolymer solution to mix evenly, emulsify, polycondense, wash, filter, and dry to obtain multi-layer capsule wall microcapsules; the number of times of adding again is one or more times;
[0052] The micron particle size of the urea-formaldehyde prepolymer solution is different when it is added again.
[0053] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0054] The different micron particle sizes in the multi-layer capsule wall structure can increase the thickness and density of the capsule wall, improve the mechanical strength and compressive resistance of the microcapsules, and enable the microcapsules to better resist external forces during transportation, stirring, coating and long-term use, reducing the risk of rupture, thereby extending the service life of the coating;
[0055] The multi-layer capsule wall can form a more uniform capsule wall structure, reducing the presence of defects and pores; the distribution and arrangement of particles of different micron sizes in the capsule wall can form a denser barrier to prevent the repair agent from being released prematurely during storage and use, thereby improving the sealing and stability of the microcapsules;
[0056] Different micron particle sizes in the multi-layer capsule wall structure can affect the release performance of the repair agent, allowing the repair agent to be released in a more controllable manner. Micron particles of different particle sizes in the multi-layer capsule wall have different response speeds to cracks. In actual use, the number of capsule wall layers and the size and distribution of the micron particle sizes contained can be adjusted according to the scope and degree of the cracks to achieve regulation of the release rate and release mode of the repair agent. When the coating is damaged, the outer capsule wall responds to the cracks and promotes the rupture of the microcapsules, while the inner capsule wall can control the release rate of the repair agent, thereby achieving more accurate and effective repair;
[0057] The multi-layer capsule wall design enables the microcapsules to adapt to different coating systems and construction conditions. The multi-layer capsule wall is stable in environments that require long-term transportation and storage. By adjusting the number of capsule wall layers and the particle size of micron particles, the binding force and compatibility between the microcapsules and the matrix resin can be adjusted, thereby improving the overall performance of the coating, making the coating less likely to fall off or peel off during long-term use, and extending the service life of the coating;
[0058] By controlling the number of additions and selecting different micron particle sizes, multilayer wall microcapsules with different numbers of layers and different particle size combinations can be prepared, the performance and response mechanism of the microcapsules can be regulated, and the adaptability and flexibility of the microcapsules can be further improved.
[0059] Embodiment 4: The above embodiment 3 improves the anti-corrosion performance and self-repairing efficiency of the coating by adding micron particles of different particle sizes into the capsule wall to form a multi-layer capsule wall, and further optimizes it to improve the self-repairing ability of the coating.
[0060] The multilayer capsule core microcapsules obtained in step S12 are added to dimethyl silicone oil, corrosion inhibitor and nanoparticles, mixed and dried to obtain multilayer capsule core microcapsules wrapped with capsule cores; the microcapsules are further placed in a urea formaldehyde prepolymer solution for emulsification, polycondensation, washing, filtering and drying to obtain multilayer composite microcapsules;
[0061] Among them, the mass ratio of urea formaldehyde prepolymer, dimethyl silicone oil, corrosion inhibitor and nanoparticles is (20-50): (8-10): (4-5): (1-5); the particle size of the micron particles in the urea formaldehyde prepolymer is 5-10 μm; the emulsification temperature is 25°C-35°C; the emulsification time is 5-20min; the pH value of the condensation emulsion is 2.0-2.5, the condensation temperature is 60°C-70°C, and the condensation time is 2-3h.
[0062] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0063] The two layers of capsule walls in the multilayer composite microcapsule contain capsule cores, i.e., repair agents, and the outermost capsule wall is easy to rupture; when the coating is damaged and needs to be repaired quickly, the multilayer composite microcapsules can be directly applied to the damaged area, and the repair agent in the capsule core layer released after the outermost capsule wall ruptures can directly repair the damage, significantly shortening the response time and improving the self-repair efficiency;
[0064] After the outermost capsule wall of the multi-layer composite microcapsule is broken and the capsule core is released for the initial repair, the inner layer still contains the complete multi-layer capsule core microcapsule, which can be used as a subsequent repair material to achieve supplementary repair, secondary repair or multiple repair of the coating. The structure of the multi-layer composite microcapsule enables the coating to self-repair after the initial damage of the microcapsule, further extending the service life of the coating;
[0065] By adjusting the number of capsule walls and cores, as well as the combination of the capsule walls and cores and the particles they contain, the release rate and pattern of the repair agent can be controlled to prepare coatings with different properties and response mechanisms; enabling the coating to adapt to different ranges and degrees of coating damage, achieving more precise and effective repairs.
[0066] The difference between the method of the comparative example and the method of announcement number CN110484042B in preparing the self-repairing super-hydrophobic nano anti-corrosion coating is that the organic fluorine-silicon modified acrylic resin, xylene, and hydrophobic nano-SiO 2 , microcapsules and platinum-based catalysts in a mass ratio of (80-100):(20-30):(1-2):(5-7):(2-4);
[0067] The self-repairing super-hydrophobic nano anti-corrosion coatings obtained in Examples 1 to 4 and the comparative example were tested for performance according to the following methods:
[0068] Adhesion is tested according to GB / T1720-1979 standard;
[0069] Contact angle test: measured with a contact angle meter;
[0070] The fracture toughness repair efficiency before and after coating repair was measured using an impact pendulum tester;
[0071] The self-repair ability is tested under different fracture degrees, where the fracture degree is the ratio of the crack depth to the coating thickness. The self-repair ability of the coating is tested when the fracture degree is 20%, 50%, and 80%. The coating self-repair rate is the percentage of the self-repair volume to the total damage volume.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A self-repairing super-hydrophobic nano anti-corrosion coating, characterized in that: It is composed of organic fluorine-silicon modified acrylic resin, hydrophobic nano-SiO2, microcapsules containing particles of different sizes, xylene and platinum-based catalyst; The core of the microcapsule is dimethyl silicone oil, a corrosion inhibitor mixture and nanoparticles, and the capsule wall is polyurea formaldehyde and micron particles; the corrosion inhibitor is benzotriazole; Both nanoparticles and micron particles include silicon dioxide and titanium dioxide; wherein the particle size of nanoparticles is nanometer-level, and the particle size of micron particles is micrometer-level.
2. A method for preparing a self-repairing super-hydrophobic nano anti-corrosion coating as claimed in claim 1, characterized in that: Specifically include: S1. Preparation of microcapsules; S11. A urea-formaldehyde prepolymer solution is prepared from urea, formaldehyde and micron particles; Specifically, urea, formaldehyde and micron particle solution are mixed in a mass ratio of (0.5-1.5): (1.5-2.5): (0.05-0.3), the pH of the mixed solution is adjusted to 8.0-9.0, and the mixture is placed at 60°C-80°C for reaction for 0.5h-1.5h, and after cooling, a surfactant with a mass fraction of 0.6%-1.3% is added, and the urea formaldehyde prepolymer solution is obtained after dilution; the particle size of the micron particles is 0.1-10μm; S12. The dimethyl silicone oil, the corrosion inhibitor and the nanoparticles are mixed and dried to obtain a capsule core, and the capsule core is added to the urea formaldehyde prepolymer solution and mixed, emulsified, polycondensed, washed, filtered, and dried to obtain a microcapsule; The mass ratio of urea formaldehyde prepolymer, dimethyl silicone oil, corrosion inhibitor and nanoparticles is (80-100): (8-10): (4-5): (1-5); the particle size of the nanoparticles is 5-100 nm; the emulsification temperature is 25°C-35°C; the emulsification time is 5-20 min; the pH of the polycondensation emulsion is 2.0-2.5, the polycondensation temperature is 70°C-75°C, and the polycondensation time is 3-4 h; S2. Preparation of self-repairing super-hydrophobic nano-anticorrosive coating; Specifically, organic fluorine-silicon modified acrylic resin, xylene, hydrophobic nano-SiO2, microcapsules and platinum-based catalyst are mixed in a mass ratio of (80-100):(20-30):(1-2):(5-7):(2-4), stirred at 1000-1500 rpm for 1-2 hours, and then ultrasonicated at 60-100 kHz for 30-40 minutes.
3. The method for preparing the self-repairing super-hydrophobic nano anticorrosive coating according to claim 2, characterized in that, The capsule core obtained in step S12 is used as the inner capsule core, and is repeatedly added into dimethyl silicone oil, corrosion inhibitor and nanoparticles to mix and dry to obtain a multilayer capsule core, wherein the number of repetitions is one or more, and the particle size of the nanoparticles during repeated addition increases with the number of additions, and the particle size of the nanoparticles of the inner capsule core is 5-10nm; the multilayer capsule core is added into a urea formaldehyde prepolymer solution for emulsification, polycondensation, washing, filtering and drying to obtain a multilayer capsule core microcapsule.
4. The method for preparing the self-repairing super-hydrophobic nano anti-corrosion coating according to claim 3, characterized in that, The particle size of the nanoparticles during repeated addition increases with the number of additions. Specifically, the particle size of the nanoparticles after repeated addition is n times the particle size of the nanoparticles in the inner capsule core, where n is the number of repeated additions; and n is less than 6.
5. The method for preparing the self-repairing super-hydrophobic nano anti-corrosion coating according to claim 2, characterized in that, The microcapsules obtained in step S12 are added again to the urea formaldehyde prepolymer solution for mixing, emulsification, polycondensation, washing, filtering and drying to obtain multi-layer capsule wall microcapsules; the number of times of adding again is one or more times.
6. The method for preparing the self-repairing super-hydrophobic nano anti-corrosion coating according to claim 5, characterized in that, The micron particle size of the urea formaldehyde prepolymer solution is different when it is added again.
7. The method for preparing the self-repairing super-hydrophobic nano anti-corrosion coating according to claim 3, characterized in that, The obtained multilayer capsule core microcapsules are added to dimethyl silicone oil, corrosion inhibitor and nanoparticles, mixed and dried to obtain capsule core-wrapped multilayer capsule core microcapsules; the microcapsules are further placed in a urea formaldehyde prepolymer solution for emulsification, polycondensation, washing, filtering and drying to obtain multilayer composite microcapsules.
8. The method for preparing the self-repairing super-hydrophobic nano anti-corrosion coating according to claim 7, characterized in that, The mass ratio of the urea formaldehyde prepolymer, dimethyl silicone oil, corrosion inhibitor and nanoparticles is (20-50): (8-10): (4-5): (1-5); the particle size of the micron particles in the urea formaldehyde prepolymer is 5-10 μm.
9. The method for preparing the self-repairing super-hydrophobic nano anti-corrosion coating according to claim 8, characterized in that, The emulsification temperature is 25°C-35°C; the emulsification time is 5-20min; the pH of the polycondensation emulsion is 2.0-2.5, the polycondensation temperature is 60°C-70°C, and the polycondensation time is 2-3h.
Citation Information
Cited By
High-temperature-resistant hydrophobic nano coating protective material and preparation method thereof
CN120005514A